Proyecto de Factibilidad para la Creación de una Empresa de Elaboración y Venta de Jugos Naturales y Aperitivos Frutales, en la ciudad de Loja - Ludeña Rosales, Denisse Estefanía (2016)
This thesis main objective is to "determine the feasibility for the creation of an enterprise development and sale of natural juices and snacks fruit, in the city of Loja", based on market research, technical, administrative, financial and evaluation. To fulfill these objectives the following methodology was used: In the literature review standards APA 6th edition, they suggest using as source the font Times New Roman, size 12, double spacing and margins of 2.54 centimeters across the sheet, used the aforementioned references are usually noted throughout this project, and the deductive method with the general analysis of all the categories set out in the theoretical framework for all studies and ending with the application of these concepts particularly used in the project. the inductive method was used in the development of the market study starting with the data through a representative sample and just reaching results, techniques are also used as the survey and interview by which information tastes and preferences was collected of families and the behavior of competition. Regarding the results we can determine that 381 surveys were carried out to the families of the city of Loja of which 206 families surveyed acquire natural juices, consuming 84 liters per year and 249 families consume fruit snacks consumed usually 97 kilos a year. With reference to the Market Study, the company will focus on the development and sale of natural juices and fruit snacks, the life of the project will be for 5 years. As for the natural juices identified that for the first year a potential of 48,518 families of which 54.07% corresponds to real demand that would give us 26,234 families will demand, effective demand is represented by the 83.20 % giving a total of 21,826 families 6 multiplied by the per capita of 84 liters of natural juice per year gives us a projected consumption of 1.823.671,89 liters of natural juice demand. While in fruit snacks for the first year we have the potential demand with an amount of 48,518 households out of which 65.35% are real families with 31,707 applicants, effective demand which is represented by 83.20% gives us as a result 26,380 families multiplied by the per capita consumption of 97 kilos of annual fruit snacks as a result gives us a projected 2,553,439.33 kilos of fruit snacks demand. On the supply side we obtain that is 28.309,41 liters of natural juice and 11,817 kilos of fruit snacks, which gives results in unmet demand for natural juices 1.795.362,47 liters and an unmet demand for fruit snacks of 2,541,622.33 kilos. The Technical study shows that the company will have an area of 60m2, capacity utilization of natural juices will be 20,080 liters, while the capacity utilization of fruit snacks will be 9,638 kilos, the company will be located in the city of Loja Ramón Pinto on the streets, between Jose Antonio Eguiguren and 10 August. In the financial study the project will require an investment of $ 17,855.05, being the unit cost of production of natural juices of $ 1.91 cents per liter while the unit cost of fruit snacks $ 3.26 cents a kilo. A profit margin of 30% natural juices will be obtained, while the profit margin of 38% fruit snacks. In the financial evaluation, it was established that the company is willing to pay a 91.49% interest on a bank loan, for every dollar it invests the company will make a profit of 34 cents of return, investment recover in within 2 years and 18 days of operation of the company, the project has a maximum rate of increase in costs of 20% 7 and a maximum percentage decrease in revenues is 15%. As understood that the company is too profitable. We also found the conclusions in which the lifetime of the project itself that is 5 years was identified and the Company "Delifrut" has an installed capacity to accommodate 24 people the day so same capacity was also determined to be the manager who will assume the posts of departmental heads because it is a newly established company. Finally, we find the recommendations that highlight establish campaigns that to publicize the main benefits of consumption of natural juices for health and personnel should use appropriate and clean uniforms to go with the quality and prestige of the company.